2001
DOI: 10.1111/j.1741-3737.2001.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

The Organization and Dynamics of Adolescent Conflict with Parents and Friends

Abstract: In telephone interviews, 212 adolescents described all disagreements arising the preceding day that involved parents or friends. Conflicts were organized in a similar manner in both relationships: Topics, resolutions, and outcomes were linked together and were usually tied to affect afterward. The specific dynamics of conflict, however, varied in a manner that reflects differences in relationship power and stability. Relative to those with friends, parent-child conflicts more often involved a combination of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 33 publications
1
86
0
8
Order By: Relevance
“…In contrast, during conflict with their parents, adolescents will be less precautious for these relationships are more likely to endure (Collins et al 1997). Indeed, adolescents report that they have more conflicts with their parents than with their friends (Adams and Laursen 2001;Furman and Buhrmester 1992;Jensen-Campbell and Graziano 2000). Also, whereas conflict with friends has been found to decline during adolescence (Collins and Laursen 1992), conflict with parents temporarily increases during early adolescence (for a review, see Collins and Steinberg 2006;De Goede et al 2008;McGue et al 2005), even though most parent-adolescent relationships remain close (Holmbeck 1996;Smetana et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, during conflict with their parents, adolescents will be less precautious for these relationships are more likely to endure (Collins et al 1997). Indeed, adolescents report that they have more conflicts with their parents than with their friends (Adams and Laursen 2001;Furman and Buhrmester 1992;Jensen-Campbell and Graziano 2000). Also, whereas conflict with friends has been found to decline during adolescence (Collins and Laursen 1992), conflict with parents temporarily increases during early adolescence (for a review, see Collins and Steinberg 2006;De Goede et al 2008;McGue et al 2005), even though most parent-adolescent relationships remain close (Holmbeck 1996;Smetana et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…This involves negative arguing and dispute, an evident dislike of the child by the parent, and aggressive problemsolving strategies [47]. According to Smetana, during adolescence, parent-adolescent conlict is more likely to include negative verbal exchanges instead of negative physical exchanges [48], with the primary reasons being about routine activities, such as homework, academic performance, curfews, and watching television [49,50], as well as about chores, appearance, politeness, inances [51], and more infrequently about autonomy and independence, parent control, and personal ethical beliefs [50]. In terms of the frequency or intensity of the parentadolescent conlict interactions, in their meta-analysis, Laursen et al [52] found that whereas conlict frequency decreased over the course of adolescence, conlict intensity intensiied reaching its peak in middle-to-late adolescence.…”
Section: Parent-adolescent Conlictmentioning
confidence: 99%
“…Measures of daily conflict derived from this instrument have been linked to adolescent self-esteem, school grades, and behavior problems (Burk & Laursen, 2005;Collins, Laursen, Mortensen, Luebker, & Ferreira, 1997;Shulman & Laursen, 2002). Differences between two-parent and single-parent households and between parent-child and friend relationships have been identified in terms of the frequency and management of daily conflict (Adams & Laursen, 2001;Laursen, 1995Laursen, , 2006. (Furman & Buhrmester, 1985) measured perceptions of relationships with mothers, fathers, and best friends.…”
Section: Instrumentsmentioning
confidence: 99%